Complex Physical Phenomenology of EDM with Technological Applications - Pavel, Topala; Nicolae, Ionescu; Laurentiu, Slatineanu; Alexandr, Ojegov; Ghiculescu, Daniel; Laurentiu, Marin; Dorin, Guzgan; Dmitri, Botnari (Current Research Progress in Physical Science Vol. 6, 2024)
The paper contains the results of theoretical and experimental research on the phenomena that take place during the interaction of pulsed electrical discharges with the electrode surfaces. The authors state that the picture of electroerosion is a complex one, it is produced under the action of heat and strong electric fields generated by "cold" and "hot" electrode spots. The removal of materials during electrical erosion is caused by the development of longitudinal and transverse capillary waves, but also by the bombardment of surfaces with particles from the work environment. Micrometallurgical processes, as well as diffusion effects, and chemical, and structural changes, occur in the processed surfaces. Based on scientific studies, new processing processes have been developed: modification of the microgeometry of surfaces for electronic emission up to 10 times, synthesis of carbonic films containing fullerenes and single-walled carbon nanotubes with a thickness of only 4-7 micrometers, possesses a number of beneficial properties such as reduction of the adhesion of the metal surface by 1.4 times, reducing the adhesion of metal surfaces; 1.4 times lowering the coefficient of friction between metal surfaces to 0.1, increasing the functionality of glass castings by 2.5-4 times, increasing the corrosion resistance of steel parts in aggressive environments by 1.5 times. Research on the surface electrical resistance and corrosion resistance of oxide and hydroxide films formed on C45 steel surfaces by applying EDM showed that the surface electrical resistance of samples increased 107 times, the corrosion potential increased from -0.44 mV to +0.4 V, the corrosion resistance increased about 2 times in 1% NaCl water solution, and about 10 times in 30% H2SO4 water solution.